Handbook of research on big data, green growth, and technology disruption in Asian companies and societies - Ordóñez de Pablos, Patricia, 1975-; Zhang, Xi (Researcher in business management), 1982-; Almunawar, Mohammad Nabil, 1960-; Labra Gayo, Jose Emilio (Advances in business strategy and competitive advantage., 2022)
"This book offers an international platform to bring together academics, researchers, lecturers, decision makers, policy makers, and practitioners to share new theories, research findings, and case studies, to enhance understanding and collaboration in business, digital strategies, disruptive innovation, green growth, and technology in Asia"--